Peran Jaringan Advokasi Football Against Racism in Europe (FARE) terhadap Konstruksi Wacana Anti Diskriminasi Ras dalam Industri Sepak Bola Eropa - Anung Riyanti; Ika Riswanti Putranti; Satwika Paramasatya (Journal of International Relations Diponegoro, 2022)
In recent years, transnational advocacy networks as actors in international relations have brought global action in an effort to construct global discourse on the issue of racism. The existence of global civil society in grassroots movements tends to be less seen as active in its involvement in international politics. This thesis aims to examine the role of the transnational advocacy network Football against Racism in Europe (FARE) in the football industry in Europe regarding its involvement in the construction of anti-racism discourse. FARE is a transnational advocacy network that accommodates anti-racism campaigns and social movements in European football to increase the influence of civil society advocacy in international politics. This research will be structured using the norm cycle theory in the constructivism paradigm which is arranged in qualitative explanative research through congruent analysis techniques. Constructivism provides an explanation of how a norm can emerge, spread, and be adopted through the norm cycle theory. FARE's anti racial discrimination discourse in the football industry in Europe will be analyzed based on the norm emerge, norm casade, and norm internalization as new elements from previous research. The hypothesis of this study is that the FARE transnational advocacy network succeeded in raising the idea of anti-racism in the international community, influencing the process of discourse construction within FIFA and UEFA in shaping policies, until these norms are internalized by clubs, countries and national football associations in Europe. The FARE movement shapes the function of global society and individuals who are involved in the FARE campaign as advocates in the form of solidarity support for marginalized voices for anti-racism human values in the football industry in Europe.